2017
DOI: 10.1186/s12955-017-0600-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation and reliability of the translated Malay version of the psychosocial impact of dental aesthetics questionnaire for adolescents

Abstract: BackgroundThis paper describes the cross-cultural adaptation of the Psychosocial Impact of Dental Aesthetics Questionnaire (PIDAQ) into Malay version (Malay PIDAQ), an oral health-related quality of life (OHRQoL) instrument specific for orthodontics for Malaysian adolescents between 12 and 17 years old.MethodsThe PIDAQ was cross-culturally adapted into Malay version by forward- and backward-translation processes, followed by psychometric validations. After initial investigation of the conceptual suitability of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(58 citation statements)
references
References 36 publications
(66 reference statements)
7
48
0
3
Order By: Relevance
“…The internal consistencies of the PIDA domains were satisfactorily and consistent with past reports (Wan Hassan et al 2017aHassan et al , 2017b. The Cronbach alpha values for the DSC (0.86), SI (0.88) and PI (0.85) domains were within the recommended range of 0.70 and 0.95 (Terwee et al 2007).…”
Section: Resultssupporting
confidence: 87%
“…The internal consistencies of the PIDA domains were satisfactorily and consistent with past reports (Wan Hassan et al 2017aHassan et al , 2017b. The Cronbach alpha values for the DSC (0.86), SI (0.88) and PI (0.85) domains were within the recommended range of 0.70 and 0.95 (Terwee et al 2007).…”
Section: Resultssupporting
confidence: 87%
“…This questionnaire measures quality of life aspects linked to oral health which are specifically linked to dental aesthetics. Devised by Klages et al in 2006 11 , the questionnaire is filled in by the patient himself/herself and is geared towards use by adolescents and young adults; it has been widely validated in different languages and cultural contexts [12][13][14][15] . Data gathering.…”
mentioning
confidence: 99%
“…While Afroz et al [5] determined that Indian men were signi cantly more concerned about their smile compared to women, and women were more satis ed with their dental aesthetics. The authors suggested that changes in the society and the impact of marketing made men concerned as women with their beauty and their physical appearance [5,22]. The diversity between these ndings and the present study could have resulted from differences in age of participants and study methods [19] or due to the ethnic and cultural differences between the studied populations [24].…”
Section: Discussionmentioning
confidence: 60%
“…Other studies didn't nd signi cant differences between males and females in regards to PIDAQ [22,23]. While Afroz et al [5] determined that Indian men were signi cantly more concerned about their smile compared to women, and women were more satis ed with their dental aesthetics.…”
Section: Discussionmentioning
confidence: 99%